Effect of Yogasan on Maansik Swasthya- A Review Article - Devi, Manu; Pareek, Gargi; Deepa; Dixit, Mahesh (International Research Journal of Ayurveda & Yoga, 2023)
The term is derived from the Sanskrit Ayur, meaning ’ life" or "longevity," and Veda, meaning "knowledge" or " science. Ayurveda is that which deals with good, bad, happy and unhappy life, its promoters and non-promoters, measure and nature). "Ayus’ means the conjunction of body, sense organs, mind and self and is known by the synonyms dhari, jivita, nityaga and anubandha. Mental health is not mere absence of mental illness, but is a state of well-being in which an individual realizes his or her own abilities, can cope with the normal stress of life, can work productively and fruitfully and is able to make a contribution to his or her community. Yoga and Asan is play an important role in Maansik Swasthya. The physical exercises (asanas) may increase patient’s physical flexibility, coordination, and strength, while the Pranayaam and meditation may calm and focus the mind to develop greater awareness and diminish anxiety, and thus result in higher quality of life. Other beneficial effects might involve a reduction of distress, Uchha Raktachap, and improvements in resilience, mood, and metabolic regulation.